Use of the esa resistance index to guide dosing for anaemia management. Issue 4 (27th March 2020) - Ross, Edward A.; Paugh‐Miller, Jennifer L.; Wen, Xuerong; Nappo, Robert W.
SUMMARY: Background: Identifying erythropoiesis‐stimulating agent (ESA) resistance is important for treating reversible causes, reaching target haemoglobin levels with minimal dosing, avoiding adverse effects and reducing costs. The resistance index (RI, dose/kg weight/g haemoglobin/dl) is reportedly superior to absolute or weight‐based dosing. Objectives: With the growing number of ESA classes and medications, our goal was to develop methodology to establish RI ranges in otherwise healthy haemodialysis patients as a structured approach to identify remediable causes of anaemia. Design: We retrospectively studied anaemia management with darbepoetin in 100 chronic haemodialysis patients and a subgroup of 48 without identifiable conditions that impair erythropoiesis. Data included inflammatory and bone marrow conditions, medications with hematologic effects, catheter use, iron, parathyroid and dialysis measures. Results: The haematologically healthy group was aged 57.1 ± 1.9 SEM years, 33% diabetic, with haemoglobin 10.4 ± 0.2 g/dl. The darbepoetin RI (DRI) values were 0.05 ± 0.01, absolute dose 38.5 ± 3.5 mcg/week and weight‐based 0.50 ± 0.05 mcg/kg. Regression analyses included iron saturation, ferritin, parathyroid hormone and urea reduction ratio. DRI was superior to other dosing approaches based on the distribution of results (kurtosis) and discordance between the measures that occurred in 17% of patients at haemoglobin target. Conclusions: We demonstrate the value of determining the RI for use with expanding ESA choices, using as an example how DRI values can be established for healthy haemodialysis patients so as to guide dosing. When elevated, the RI can trigger evaluation for remediable factors causing hyporesponsiveness even when haemoglobin goals have been reached.